Peptides of Trypsin Hydrolyzate in Bovine Colostrum - Sergei L. Tikhonov; Natalia V. Tikhonova; Khatam Kh. Tursunov; Irina G. Danilova; Vladimir A. Lazarev (Техника и технология пищевых производств)
Bovine colostrum contains biologically active substances, e.g., immunoglobulins, peptides, and cytokines, which makes it a logical component of numerous functional products. Colostrum peptides also possess antimicrobial activity. This bioavailability increases during colostrum fermentation with proteolytic enzymes. The research objective was to describe peptides isolated from the trypsic hydrolyzate supernatant of bovine colostrum and to evaluate their antimicrobial and antifungal properties. The supernatant of trypsin hydrolyzate of bovine colostrum was isolated by centrifugation at 3900 rpm for 7 min. The supernatant was separated by preparative chromatography. Its peptide composition was determined on a MALDI-TOF mass spectrometer, while the protein sequences were deciphered using the Mascot database. Proteins were precipitated with ammonium sulfate, and the antimicrobial activity was measured by the disk-diffusion method against gram-positive and gram-negative bacteria and dipoloid fungi. Strains were cultivated on a thick LB nutrient medium at 37°C. The antimicrobial activity was defined experimentally on Wistar rats infected intraperitoneally with Salmonella enteritidis 92. The trypsin hydrolyzate supernatant of bovine colostrum revealed four peptides, one of which belonged to short peptides, while the remaining three belonged to polypeptides. The isolated peptides had different molecular weights of 8.4, 6.5, 13.0, and 18 kDa. The enzymatic hydrolyzate proved bactericidal against Escherichia coli and Bacillus subtilis and demonstrated antifungal activity against Candida albicans. When rats infected with S. enteritidis 92 were administered with trypsin hydrolysate, it promoted their survival, decreased LD50, and increased the mean day of death period from 2 to 4 days. The research proved the antimicrobial effect of colostrum peptides and suggested their immunotropic properties. The peptides obtained from the trypsin hydrolyzate supernatant of bovine colostrum can be recommended for functional food industry as part of antimicrobial products.